PENGARUH KOMITE AUDIT, KUALITAS AUDIT, LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP KUALITAS LABA PADA PERUSAHAAN INDUSTRY & CHEMICAL YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2014 - Aryengki, Rio; Satriawan, Raja Adri; ', Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This reserch aims to examine the influence of the audit commite, audit quality, liquidity and company size which earning quality. This study uses secondary data. Data collection technique used is documentation. Data analysis method used is classic assumption test. Sample selection technique used is purposive sampling. 31 companies listed in Indonesia stock exchange from 2011 to 2014. The analytical method is multiple linear regression using SPSS version 18. The influenced audit commite variable for the earnings quality were 0.003, audit quality for the earnings quality were 0.001, liquidity for the earnings quality were 0.000, have a significant influence on earnings quality. Meanwhile company size for the earnings quality were 0.973, the result show that company size wasn’t significant effect. The big influence of audit commite, audit quality and liquidity were 74.40%.Keywords : Audit Commite, Audit Quality, Liquidity and Company Size